Looking ahead: new approaches to medieval Iberian heritage. Issue 2 (2nd July 2016) - Miguélez Cavero, Alicia
ABSTRACT: This special issue, "Looking ahead: new approaches to medieval Iberian heritage", is the main output of a fruitful collaboration between the humanities and the experimental sciences, which has greatly contributed to increase our knowledge of creative processes in medieval Iberia. The articles examine a wide range of objects produced using very different media, such as illuminated manuscripts, glass, monumental painted altarpieces and azulejos (glazed tiles). Some of these objects were studied for the first time in the framework of this project, while others had received very little attention previously. Moreover, several of the case studies concern unfinished works, which gives us an opportunity to better approach the creative processes. This introductory article aims to establish the main overarching themes that have emerged from the joint efforts of the participating scholars and teams. These themes include the multicultural context of medieval Iberia, a revision of the traditional notion of the medieval workshop, a consideration of the materials used to construct colours and molecular palettes, and the transfer of technological processes between the different cultural and religious horizons that coexisted in the Iberian Peninsula. This paper also investigates the new avenues of research that the articles have opened, such as the role played by medieval Iberia in a broader European, Mediterranean and global context regarding the arrival of precious materials from the Far East.